Employment & Economic Growth : An International Perspective - Morse, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1969)
In its anniversary year, the I.L.O. has launched a World Employment Programme. The author will examine the circumstances in which this Programme has been launched and what it must accomplish. After a brief discussion of the nature and extent of unemployment and underemployment in developing countries, the author will make some remarks on the kind of approach that these countries themselves may have to adopt in grappling with these problems. He will then present the relationship between employment and growth. Finally he will make some comments on the kind of international perspective and international programme that are needed. This papers was presented by the author at Columbia University, as part of the Gabriel Silver Memorial Lecture.